Super superstitions - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Stranger than fiction., 2019)
Surveys ten superstitions people have believed from around the world, such as people believing sitting on the ground would bring bad luck, or that urine had magical properties, and that babies born with hair were bad luck or would be stubborn.